Construction of a combined enzyme system of graphene oxide and manganese peroxidase for efficient oxidation of aromatic compounds. Issue 14 (31st March 2020) - Yang, Shichao; Yang, Jun; Wang, Tao; Li, Liuqing; Yu, Siming; Jia, Rong; Chen, Ping
Abstract : We report a highly efficient catalyst by a combination of graphene oxide and manganese peroxidase from Irpex lacteus F17 for the oxidation of aromatic substances and dye decolorization. Abstract : Manganese peroxidase (MnP) from Irpex lacteus F17 has potential use as a biocatalyst in the field of environmental biotechnology because of its unique properties and ability to decompose harmful aromatic compounds. However, its requirement of harsh acidic reaction conditions and its insufficient catalytic activity restrict its practical applications. Here, we combine graphene oxide (GO) and MnP to construct an efficient enzyme system (GO-MnP) with improved catalytic efficiencies and a wide pH range for the oxidation of aromatic substances and dye decolorization. We found that the Michaelis constant ( K m ) of GO-MnP for Mn 2+ was 2.8 times lower and the catalytic efficiency ( k cat / K m ) of GO-MnP was 4.5 times higher than those of MnP, and that the decolorization of various dyes by GO-MnP was significantly improved over the pH range of 4.5–5.5. A comparison of the midpoint redox potentials also reflects the strong oxidation ability of GO-MnP. Furthermore, we demonstrated that, in the GO-MnP system, the MnP activity is mainly determined by the amounts of epoxy and carboxyl groups in GO, based on an analysis of the functional group changes in GO and reduced GO associated with different reduction degrees as shown by X-ray photoelectron spectroscopy.